NONVERBAL COMMUNICATION CUES OCCURRENCES IN ENGLISH JOB INTERVIEW - Luh Eka Susanti; Muhamad Nova (PROJECT (Professional Journal of English Education), 2023)
Language and nonverbal communication play a significant role in a job interview. While a candidate uses English to elaborate their answer to the questions given by the interviewer, nonverbal communication delivers a signal to the interviewer regarding the candidate’s personality, behavior, and attitude. The current study explored the occurrences of nonverbal communication cues in an English job hotel interview by applying qualitative study design. The study gathered the data from three informants who work in hotel’s human resources department. The data were gathered through interview and were analyzed using qualitative analysis method, including data reduction, data display, and conclusion drawing. The result of the study revealed that many candidates use some nonverbal communication cues during the English interview, including body language and gestures, facial expressions, eye contacts, and voice tones. These cues helped the interviewer to gain better interpretation toward the candidate’s answers. Therefore, in attending an English job interview, candidates should be aware of the nonverbal communication knowledge. Keywords:  English; Job Interview; Nonverbal Communication Cues